Peran Filsafat Pendidikan dalam Era Pembelajaran Abad 21 - Oktobianti, Anisa; Ismail, Ismail (LPPM Universitas Ekasakti, 2024)
Finding out what educational philosophy is for in this new age of learning is the primary goal of this research. The research approach used is literature review, which entails gathering and analysing a variety of pertinent sources and documents pertaining to the issue at hand. The results demonstrate that scientific philosophy plays a significant role in education in the modern day. Learning the fundamentals of science, honing one's capacity for critical thinking, and tackling the complexity and transdisciplinary problems plaguing contemporary science are all aided by educational philosophy. Modern pedagogy places an emphasis on skill development via guided learning experiences. Assertive reasoning, critical thinking, metacognition, communication, collaboration, progress, and innovation are six of the core competencies that students should strive to acquire in a student-centered, 21st-century classroom. talents with data. Since learning in the modern day is more integrated with information and abilities, training is thought to be able to generate data innovation professionals with high-quality human resources and fresh viewpoints.